Improving Public Understanding about Chronic Hepatitis and Diabetes Mellitus in The Era of The Covid-19 Pandemic - Effendy Effendy; Agus Aan Adriansyah; Akas Yekti Pulih Asih; Budhi Setianto; Evy Afifah Syagran; Iqbal Firdaus; Nikmatus Sa’adah (To Maega : Jurnal Pengabdian Masyarakat, 2023)
Hepatitis is an inflammation of the liver. In chronic hepatitis, inflammation of the heart lasts for at least 6 months. Several incidences of disease in hepatitis require good and simultaneous treatment. To increase public knowledge regarding hepatitis, a webinar was held "What and How is Chronic Hepatitis and Diabetes Mellitus in the Era of the Covid-19 Pandemic". The implementation of this community service was carried out at the Surabaya Ahmad Yani Islamic Hospital, in June-October 2022. This community service was carried out through webinar activities which were attended by 156 participants, followed by patients and non-patients which were packaged in an attractive manner in order to provide clearer information related to hepatitis and diabetes mellitus so that they are more aware and alert. The results of the webinar related to the explanation of chronic hepatitis and diabetes mellitus during the covid-19 pandemic have gone well. Evaluation of respondents' knowledge when participating in webinar activities has increased. Respondents have good knowledge regarding chronic hepatitis, transmission media for chronic hepatitis, how to prevent it, symptoms of diabetes mellitus, clean and healthy living behavior for diabetes mellitus prevention, and a good diet. Webinars held packed with interesting with webinar media you can increase the knowledge participant go on by 12%, expected through education carried out by the YouTube channel could realize a society that is more aware and care about the incidence of chronic hepatitis and diabetes mellitus. This community service activity is expected to be presented periodically with other disease topics to increase public knowledge and understanding regarding diseases, their causes, methods of prevention and treatment.